AUSTRALIA'S SECURITY STRATEGY IN RESPONDING TO CHINA'S THREAT IN THE INDO-PACIFIC REGION THROUGH THE 2021-2024 AUKUS - Saraswati, Dewi Kania; Indrawati, Indrawati (Journal of Social Politics and Governance (JSPG), 2025)
This research analyzes Australia's security strategy in responding to China's threat in the Indo-Pacific Region through the AUKUS alliance from 2021 to 2024. Amid rising geopolitical tensions and China's assertive actions, Australia faces strategic pressure that compels it to strengthen its national defense. Using qualitative methods and secondary data analysis, this study applies Alliance Theory and Bandwagoning to examine Australia's choice to align with the United States and the United Kingdom. The findings reveal that AUKUS is a deterrence strategy embedded within Australia's defense policies: Defense Strategic Update 2020, Defense Strategic Review 2023, and National Defense Strategy 2024. These policies reflect a shift from diplomatic multilateralism to military-based alliances, highlighting Australia's increasing dependency on great powers for strategic security. Through AUKUS, Australia is strengthening its defense posture, especially about nuclear-powered submarines and emerging technologies, to uphold regional stability and sovereignty. This study examines how middle powers navigate great competition through strategic security alliances.